2019
DOI: 10.3382/ps/pey355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genotype and sex on technological properties and fatty acid composition of duck meat

Abstract: Study was conducted to determine the effects of genotype and sex on the technological properties and fatty acid composition of duck meat. Native (n = 15) and Peking (n = 15) ducks were slaughtered at 10 wk old, and meat samples were taken from M. pectoralis major (breast) and M. peroneus longus (thigh). The pH24, drip loss, expressed juice, cooking loss, Warner-Bratzler shear force (WBSF), color variables, fatty acid composition, and sensory characteristics were examined. Ultimate pH of breast meat in Peking d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
8
28
2
Order By: Relevance
“…Similar results were found by Baeza et al (2010) in France in a study on the Muscovy duck meat characteristics. This age effect on pH was also observed by Baeza et al (2000) in France in Mullet ducks and by Onk et al (2018) in the Pekin ducks in Turkey. Usually, duck meat ultimate pH value is between 5.6 and 5.9 (Baeza et al, 2013).…”
Section: Effect Of Age On Ph Temperature and Water Holding Capacitysupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were found by Baeza et al (2010) in France in a study on the Muscovy duck meat characteristics. This age effect on pH was also observed by Baeza et al (2000) in France in Mullet ducks and by Onk et al (2018) in the Pekin ducks in Turkey. Usually, duck meat ultimate pH value is between 5.6 and 5.9 (Baeza et al, 2013).…”
Section: Effect Of Age On Ph Temperature and Water Holding Capacitysupporting
confidence: 73%
“…The same trend was observed by Baeza et al (2000) in France studying the sex effect on the technological meat traits of Mullet duck which is a crossbreed from Muscovy duck and Pekin duck. On the other hand, no effect of sex on pH has been reported by Onk et al (2018) in Pekin ducks in Turkey. Similarly, in China, obtained in a study on Chaohu duck meat traits that males and females' pH were similar.…”
Section: Effect Of Sex On Ph Temperature and Water Holding Capacitymentioning
confidence: 85%
“…It can also be concluded that ducks fed based on YL were characterised by faster growth of muscle tissue, which resulted in a higher content of collagen. Onk et al (2018) analysed FA composition in 10-week-old ducks of various genotypes. They reported a lower content (under 20%) of linoleic acid (C18:2 n-6) in both treatment groups compared to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that duck sex has no influence on the fatty acid composition of breast meat [29,30]. However, other study indicated that sex, as a main effect, had significant influence on proportions of C18:0, C18:1n-9, C18:2n-6, MUFA and PUFA [10]. Further studies were required to Principal component analysis (PCA) of fatty acid concentration in this study revealed that both breeds and developmental stages have an influence on the deposition of fatty acids in duck breast muscle.…”
Section: Effect Of Age Sex and Breeds On The Accumulation Of Fatty Amentioning
confidence: 98%
“…It has been widely reported that the fatty acid composition of meat can be affected by various factors such as age, sex, and rearing conditions of the animals [7][8][9][10]. In addition, fatty acid compositions are heritable traits, with heritability ranging between 0.2 and 0.6 in various populations of pigs [11,12].…”
Section: Introductionmentioning
confidence: 99%